2015
DOI: 10.18632/oncotarget.4114
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor binding protein 5 (IGFBP5) functions as a tumor suppressor in human melanoma cells

Abstract: The insulin-like growth factor binding protein 5 (IGFBP5), which is often dysregulated in human cancers, plays a crucial role in carcinogenesis and cancer development. However, the function and underlying mechanism of IGFBP5 in tumor growth and metastasis has been elusive, particularly in malignant human melanoma. Here, we reported that IGFBP5 acts as an important tumor suppressor in melanoma tumorigenicity and metastasis by a series of experiments including transwell assay, xenograft model, in vivo tumor meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
76
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 55 publications
7
76
1
1
Order By: Relevance
“…SOX2, CD133 and Nestin have been reported as cancer stem cell markers in melanoma (19)(20)(21). In the present study, the tumor cells of undifferentiated MM expressed CD133 and SOX2.…”
Section: Discussionsupporting
confidence: 64%
“…SOX2, CD133 and Nestin have been reported as cancer stem cell markers in melanoma (19)(20)(21). In the present study, the tumor cells of undifferentiated MM expressed CD133 and SOX2.…”
Section: Discussionsupporting
confidence: 64%
“…Recent studies have demonstrated that IGFBP5 might be a useful biomarker for cancerous tissue and metastasis [3137], but it also shows the opposite effects depending on cancer cell type and expression method [30, 4346]. In colon cancer, a study using the rat model revealed that IGFBP5 is one of the top upregulated genes [35].…”
Section: Discussionmentioning
confidence: 99%
“…IGFBP‐3 and ‐5 are the massive and conserved secreted proteins in the family of IGFBPs, which could transfer to the nucleus through a nuclear localization sequence . It has been implicated that dysregulated IGFBP5 may involve the carcinogenesis and progression of several carcinomas, for example, oral carcinoma and breast carcinoma . More importantly, IGFBP6 has been verified to be a new causal variant of DD .…”
Section: Introductionmentioning
confidence: 99%